Customization of an instrumented ergometer paddle to be synchronized with a customized footrest and foot-strap to assess upper- and lower-body force contributions during paddling - Nishimura, Sean (Nanyang Technological University, 2021)
Canoe sprint is a sport where athletes compete against one another by paddling a canoe or kayak over flat water in an event known as flat-water racing. It is an Olympic sport where athletes compete over four distances ranging from 200 meters to 5000 meters as an individual, a pair or a team of four. Speed is key in this sport to be successful and strength contributes to speed. By effectively translating the forces created from the upper and lower body, athletes will be able to attain high velocities throughout the race. Many researches have featured contributions of upper body strength but few on lower body or the combination of the upper body and lower body. Since the lower limb muscles are a bigger muscle group compared with the upper limbs, it will be beneficial for the athletes to know the not only the strength contributions from the upper body but also the lower body during kayaking. The aim of this study is to determine the forces generated in a push and pull action during paddling as well as the forces generated from the upper body through the paddle, and combine it using a software to provide immediate and synchronized feedback. This will help the athletes to analyse their abilities to generate force through their upper and lower bodies during kayaking. The project aims to redesign a previously instrumented footrest and footstrap, as well as paddle, to be mounted on the actual kayak and tested on-water with wireless transmission. This project builds on the work completed by predecessors over four FYPs.